Decision‐making strategies in fixed‐block railway signaling systems: A discrete event systems approach - Takai, Shigemasa; Söylemez, Mehmet Turan; Durmuş, Mustafa Seçkin (Wiley, 2014)
Ensuring the system safety at all times is most important in railway systems where small failures may result in a large number of casualties and property loss. Although there are various design methods, safety precautions, and recommendations of the railway‐related safety standards, sometimes the occurrence of accidents cannot be prevented. In this paper, according to the recommendations of the railway‐related safety standards, an interlocking system architecture, which consists of two controllers and a coordinator, for a fixed‐block railway signaling system is studied. Based on the Petri net models of railway field components, decision‐making strategies including fault diagnosis are presented. © 2014 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.
Keywords: Safety engineering; Failure analysis; Standards; Interlocking systems; Fixed-block railway signaling systems; Safety standard; Petri nets; Transportation; Discrete event simulation; Safety-related standards; Railroad signal systems; Railroads; Fault diagnosis; Safety precautions; Field components; Petri net models; Railroad transportation; Decision-making strategies; Safety-Related; Railroad accidents; Decision making; Fault detection; Railway signaling systems